HCA PIECESTM Care Coach Program: Peer-to-peer approach to promote person-centred care in long-term care - Jones, Jae Yon; Leddy, Amanda; Real, Gloria (Healthcare management forum, 2025)
In Long-Term Care (LTC) settings, the potentially inappropriate use of antipsychotics for behavioural and psychological symptoms of dementia is a persistent issue, with high rates despite limited benefit and serious risk. Best practice is a non-pharmacological, person-centred approach to care, though this can be challenging in LTC settings. To help address this gap, we developed the PIECESTM HCA Care Coach Program and described its implementation and outcomes observed at 13 LTC homes. This program empowers healthcare aides with training, tools, and processes to practice the principles of person-centred care and provide peer mentorship to the care team. After one year, we found declining antipsychotics use (by 4.4%) and positive indicators of improved staff experience and improved resident quality of life. The Care Coach Program can be adapted and spread to a variety of LTC settings to help reduce potentially inappropriate antipsychotic use and better support people living with dementia.